Modulating thermal load through lightweight residential building walls using thermal energy storage and controlled precooling strategy. (5th November 2020) - Kishore, Ravi Anant; Bianchi, Marcus V.A.; Booten, Chuck; Vidal, Judith; Jackson, Roderick
Highlights: Optimal precooling strategy for lightweight residential buildings. PCM-integrated building walls under various precooling conditions are examined. Influence of precooling on key building energy performance parameters is evaluated. Up to 95% reduction in heat gain during peak hours using optimized precooling strategy. Abstract: Precooling is a recognized technique for reducing cooling energy in buildings during peak hours by shifting load to off-peak hours. This technique is particularly effective in buildings with high thermal mass, because of their large thermal energy storage capacity, and in commercial buildings due to their variable electricity pricing based on time-of-use rates. Precooling in residential buildings has been a matter of limited interest in the past because of their low thermal mass and typically uniform electricity pricing rate. While previous studies on precooling primarily focused on cost savings, an important aspect of precooling is the thermal load modulation, which could be very effective in managing peak demand in lightweight residential buildings integrated with thermal energy storage systems. In this study, we examine different precooling strategies to manage the heat gains in lightweight building walls integrated with phase-change materials. We create nine different precooling profiles by controlling the interior temperature, and then evaluate the influence of the precooling profiles on four key building energy performance parameters: total heat gain, peak heat gain, maximum heat gain during peak hours, and time at which peak occurs. To thoroughly understand the fundamental physics, we first consider hypothetical climates and obtain the optimal precooling strategy required to achieve maximum peak shedding and shifting while minimizing the total heat gains. We then extend the model to Baltimore, Maryland, and estimate the benefits of the optimized precooling strategy under real conditions. The optimal precooling strategy proposed in this study can shift the peak heat gain by up to 14 h, thereby reducing the heat gain during peak period by up to 95%, at the expense of 23% increase in the total heat gains.